Análise e estimativa das componentes da radiação solar através de dados medidos na rede EPESOL da UTFPR no estado do Paraná - Souza, Muriele Bester de (2020)
This research features the monitoring of the installation of standard SONDA (System of National Organization of Environmental Data) and standard EPE (Energy Research Company) Solarimetric Stations, implanted in six campuses of the Federal University of Technology – Parana (UTFPR) representing in general, the different microclimates in the state of Paraná and which aims to fill an important gap in the researches regarding to the lack of surface quality solar radiation data in the state. The implanted stations compose UTFPR’s Solar Energy Research Stations Network (EPESOL), which were installed in the municipalities of Curitiba, Campo Mourão, Cornélio Procópio, Medianeira, Pato Branco and Ponta Grossa. This study performed the collection and analysis of the data provided by these stations which were validated with the data presented by the Atlas of Solar Energy of the State of Paraná (2017) and provided by the National Meteorology Institute (INMET). The values of diffuse, DNI (Direct Normal Irradiance) and global radiation were also estimated for the tilted surface at latitude angle, using consolidated models and through an equation to estimate the diffuse radiation proposed by the author for the city of Curitiba, where the horizontal global radiation is used as an input variable. As a result, variations of around 1.0% were noticed in the measured values of horizontal global radiation between SONDA and EPE stations implanted in Curitiba, whose installed pyranometers have different degrees of accuracy (SONDA: secondary standard – CMP10; EPE: first class CMP6). It was verified for all cities that the global average daily horizontal radiation measured in March, April, May and July 2020 was higher than the Atlas, with percentage variation of the global irradiation on horizontal plane in the period between 8,0% and 16.3%, meaning that in the given months the state of Paraná received more radiation than expected. Regarding the data presented by INMET, it was verified that the values measured by both stations (SONDA / EPE and INMET) were similar, evidencing consistency in the data, with a minimum percentage variation of 0.3% in Medianeira / INMET and a maximum of 11,4% in Cornélio Procópio / INMET. Regarding the data estimated by the models, they were validated through statistical indicators whose indexes presented some good and excellent results for the estimates of the global irradiations in the tilted surface and DNI (the last validated only by the SONDA stations), except in Cornélio Procópio, where the relative root mean square error (rRMSE) was above 30% and the models for estimating the global irradiation in the tilted surface were classified as weak in this location according to the Atlas. The equation proposed by the author and the model by Erbs et al. (1982) to estimate diffuse radiation obtained good results, with 20% ≤ rRMSE ≤30%.